2021
DOI: 10.3390/su132011320
|View full text |Cite
|
Sign up to set email alerts
|

A Framework to Evaluate the SDG Contribution of Fluvial Nature-Based Solutions

Abstract: Nature-based solutions (NBSs) are measures reflecting the ‘cooperation with nature’ approach: mitigating fluvial flood risk while being cost-effective, resource-efficient, and providing numerous environmental, social, and economic benefits. Since 2015, the United Nations (UN) 2030 Agenda has provided UN member states with goals, targets, and indicators to facilitate an integrated approach focusing on economic, environmental, and social improvements simultaneously. The aim of this study is to evaluate the contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…The solution supports to five indicators of the sixth goal on sustainable management of water; and six indicators of the eleventh goal on making cities safe, resilient and sustainable. The results of our SDG analysis are similar to whatAndrikopoulou et al (2021) found when applying their framework to identify the SDG contribution of fluvial nature-based solutions.…”
supporting
confidence: 83%
See 1 more Smart Citation
“…The solution supports to five indicators of the sixth goal on sustainable management of water; and six indicators of the eleventh goal on making cities safe, resilient and sustainable. The results of our SDG analysis are similar to whatAndrikopoulou et al (2021) found when applying their framework to identify the SDG contribution of fluvial nature-based solutions.…”
supporting
confidence: 83%
“…Although the proposed solution provides a plethora of benefits compared to traditional engineering flood management solutions, it still has its disadvantages. Wetlands, for example, require a large land footprint; they require more time for water treatment compared to traditional technologies and are associated with more uncertainties and vulnerabilities being dependent of natural resources to function (Andrikopoulou et al 2021;Haddis et al 2020;Oral et al 2020;Rigotti et al 2020). All of these requirements limit the large-scale implementation of nature-based and hybrid solutions despite their proved environmental superiority (Haddis et al 2020;Oral et al 2020).…”
Section: Limitations and Application Range Of The Proposed Solutionmentioning
confidence: 99%
“…Likewise, they allow for a performance assessment based on a common set of criteria. Within this study, the SDG-SIS (Schipper et al, 2017, Andrikopoulou et al, 2021, Schipper et al, 2021) was used in combination with IPCC climate change projections to measure the performance of multiple NbS sites in the context of climate adaptation. Secondly, the management plans of these NbS sites are evaluated on SDG recognition in the evaluation of planned sustainable development.…”
Section: Discussionmentioning
confidence: 99%
“…Schipper et al (2021) integrates relevant SDG targets within an assessment framework to analyse global NbS case studies on coastal flood risk management with biodiversity goals. This assessment framework, called the SDG-Sustainability Impact Score (SDG-SIS), has been applied to analyse the sustainability of NbS sites, including coastal riverine areas (Andrikopoulou et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…To achieve success, such assessments must be transdisciplinary (for example, including hydrology, geomorphology, healthcare, ecotoxicology, civil and chemical engineering, sociology, economics and GIS) and integrally involve indigenous knowledge, community involvement and direction. Indeed, incorporation of the impacts of floods, and nature-based solutions for river flood risk mitigation, is inherent within many of the UN's Sustainable Development Goals (SDGs) 16 . Real progress towards achieving the SDGs will be undermined unless the impacts on human health are quantified more fully with respect to the geomorphic and healthcare landscapes on which they are situated.…”
Section: Riverine Landscapes and Human Healthmentioning
confidence: 99%